2024
DOI: 10.1063/5.0185499
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substrate-induced defects on structural and resistive switching properties in Gd0.2Ca0.8MnO3 thin films

I. Angervo,
A. Antola,
A. Schulman
et al.

Abstract: Gd0.2Ca0.8MnO3 thin films were deposited on various substrate materials and their structural and resistive switching (RS) properties were investigated. The deposition resulted in epitaxial and polycrystalline films, with the latter also exhibiting distorted film surfaces. Both epitaxial and a part of polycrystalline films used as RS devices showed consistent RS performance in which an order of magnitude, or higher, switching ratios were achieved between high and low resistance states. The devices showed strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…Our previous research has already shown the existence of RS characteristics in GCMO, prepared both by PLD and CSD, on single crystal STO substrates [23,30,40]. The phenomena are again confirmed here in addition to the Si/STO substrate as well for both deposition methods as depicted in figure 4(a) for PLD and (c) for CSD-prepared films on STO.…”
Section: Resistive Switching Properties In Planar Memristorssupporting
confidence: 86%
See 2 more Smart Citations
“…Our previous research has already shown the existence of RS characteristics in GCMO, prepared both by PLD and CSD, on single crystal STO substrates [23,30,40]. The phenomena are again confirmed here in addition to the Si/STO substrate as well for both deposition methods as depicted in figure 4(a) for PLD and (c) for CSD-prepared films on STO.…”
Section: Resistive Switching Properties In Planar Memristorssupporting
confidence: 86%
“…It is noted that due to apparent instability in PLD Si/STO the bipolar nature of the RS becomes indistinct. However, in our previously published research the bipolar RS is apparent in an identical device [40]. Similarly, to what was observed in PLD, CSD STO (c) demonstrates improved performance over CSD Si/STO (d), indicating that the STO buffer layer incorporated in the silicon substrate significantly reduces RS characteristics, which corresponds to a decrease in the film crystal quality.…”
Section: Resistive Switching Properties In Planar Memristorssupporting
confidence: 76%
See 1 more Smart Citation